Indonesia’s Quiet Diplomacy Towards Rohingya: An Effective Way In Resolving Humanitarian Crisis - Naeli Fitria (Journal Research of Social Science, Economics, and Management, 2023)
The current Rohingya situation has been addressed through international initiatives. Quiet diplomacy transitions to loud diplomacy. The situation in Rakhine State has improved because of such diplomatic advances. This essay sought to examine Indonesia's approach to helping Rohingya through humanitarian aid. This study will investigate the mechanism of mediation and its particular techniques, such as multi-party involvement, manufactured discourse, and fourth parties, using the Quiet Diplomacy approach. The contribution of Indonesia also covered in this paper mainly related to interfaith dialogue. The research in this study shows that Indonesian engagement in global, regional, and national collaborative collaboration is having a substantial impact on reducing tension in the Rakhine States.